Wild yak Bos mutus in Nepal: rediscovery of a flagship species - Acharya, R; Ghimirey, Y; Werhahn, G; Kusi, N; Adhikary, B; Kunwar, B (De Gruyter, 2015)
Wild yak Bos mutus is believed to have gone extinct from Nepal. Various searches in the last decade failed to document its presence. In Humla district, far-western Nepal, we used observation from transects and vantage points, sign survey on trails, and informal discussions to ascertain the presence of wild yak in 2013 (May–June) and 2014 (June–July). Direct sightings of two individuals and hoof marks, dung piles, pelts, and head of an individual killed in 2012 confirmed its presence. The wild yak has an uncertain national status with confirmed records only from Humla district. Further research in the higher Himalayan regions of Humla and other districts is urgently needed to evaluate wild yak status combined with immediate conservation actions to protect the remaining individuals.